Performance augmentation of triangular solar still using sensible energy storage materials: thermo-exergo-economic and sustainability analyses - Sharma, Naveen; Patel, Ashutosh; Deep, Raman; Gautam, Shivam (Comptes Rendus. Chimie)
People in remote areas often struggle with limited access to potable water. This experimental research aims to augment the performance of a triangular solar still (TSS) by incorporating sensible heat storage materials (SHSMs) for sustainable freshwater production. Four different configurations—standard TSS, TSS with bricks (TSS-B), TSS with paper napkins wrapped around the brick (TSS-NB), and TSS with sand bed (TSS-S)—were tested under the climatic conditions of New Delhi (28° 35' N, 76° 54' E), India, during October 2023. The performance of TSS was assessed based on energy, exergy, economic, and environmental parameters. From experimental results, it was observed that the daily yield of the TSS-S was 3.12 L/m2, which is about 81.40% higher than that of TSS. Additionally, the daily yield increased by around 34.86% for TSS-B and about 28.23% for TSS-NB than TSS. Incorporating SHSMs into the TSS led to significant enhancements in energy efficiency (19.15% to 75.12%) and exergy efficiency (7.41% to 36.44%) compared to TSS, solidifying it as a viable choice for freshwater production. The economic assessment revealed that employing SHSMs resulted in a reduction in the cost per liter of freshwater generation by up to 42.86% (for TSS-S) and a corresponding decrease in the payback period by up to 44.33% (for TSS-S) compared to TSS. Furthermore, the exergetic sustainability of the TSS was explored using improvement potential and sustainability index parameters. Moreover, the TDS and pH values of the yield produced from TSS, with and without SHSMs, adhere to water quality standards.